From Kotoński to Duchnowski. Polish electroacoustic music - Kominek, Mieczysław (Interdisciplinary Studies in Musicology, 2018)
Founded in November 1957, the Experimental Studio of Polish Radio (SEPR) was the fifth electronic music studio in Europe and the seventh in the world. It was an extraordinary phenomenon in the reality of the People’s Poland of those times, equally exceptional as the Warsaw Autumn International Festival of Contemporary Music, established around the same time - in 1956. Both these ‘institutions’ would be of fundamental significance for contemporary Polish music, and they would collaborate closely with one another. But the history of Polish electroacoustic music would to a large extent be the history of the Experimental Studio. The first autonomous work for tape in Poland was Włodzimierz Kotoñski’s Etiuda konkretna (na jedno uderzenie w talerz) [Concrete study (for a single strike of a cymbal)], completed in November 1958. It was performed at the Warsaw Autumn in i960, and from then on electroacoustic music was a fixture at the festival, even a marker of the festival’s ‘modernity’, up to 2002 - the year when the last special ‘concert of electroacoustic music’ appeared on the programme. In 2004, the SEPR ceased its activities, but thanks to computers, every composer can now have a studio at home. There are also thriving electroacoustic studios at music academies, with the Wroclaw studio to the fore, founded in 1998 by Stanisław Krupowicz, the leading light of which became Cezary Duchnowski. Also established in Wroclaw, in 2005, was the biennial International Festival of Electroacoustic Music ‘Música Electrónica Nova’.